The Effect of Meru Chikitsa (healing therapy) on Chronic Low Back Pain: A Case Series - Anita Jagetia (Indian Journal of Integrative Medicine, 2023)
Chronic low back pain (CLBP) is a frequent cause of disability and it represents a medical, social and economic burden globally. All the patients suffering from low backache due to grade 1 or 2 disc may not require surgery. They are subjected to conservative treatment, which alone may not be very effective all the time. The objective of this case series is to assess the effectiveness of an Ancient Ayurveda healing touch therapy called Meru Chikitsa (MC) in adult patients with moderate to severe Back pain issues. The pain was analyzed by using scales such as the Visual Analogue Scale (VAS), BECK’s depression inventory, and 36-item-short-form survey (SF-36 score). All 9 patients were given sessions of Meru Chikitsa for 15 days. Pre-assessment was done before starting the therapy and clinical assessment was done post-15 days of treatment. The results have been very encouraging and there has been considerable improvement in all the patients. This is the first reported case series on results of MC. It can be extended with bigger studies and with various neurological disorders.